Effect of printing parameters on the electromagnetic shielding efficiency of ABS/carbonaceous-filler composites manufactured via filament fused fabrication. (May 2021) - Schmitz, D.P.; Dul, S.; Ramoa, S.D.A.S; Soares, B.G.; Barra, G.M.O.; Pegoretti, A.
Highlights: FFF to manufacture polymer composites samples for EMI SE application. Printing patterns influence sample's electrical conductivity and EMI SE. Layer high influences sample's shielding effectiveness. Increase in CNT amount improves samples electric and electromagnetic properties. Abstract: This work assesses the influence of material composition as well as printing parameters on the electromagnetic interference shielding effectiveness (EMI SE) of polymeric composites based on poly(acrylonitrile-co-butadiene-co-styrene) (ABS) filled with carbon nanotubes (CNT) and/or carbon black (CB), manufactured via fused filament fabrication (FFF). In the study three compositions were analyzed, ABS with 5 wt% of CNT, ABS with 5 wt% of CB, and a hybrid composite with also 5 wt% total of additive but a (75:25) fraction of CNT:CB. The materials properties were evaluated on samples printed in three different growing directions, horizontal concentric (HC), perpendicular concentric (PC) and horizontal at ±45° (H45). The electrical conductivity of the printed samples are highly influenced by the CNT presence in the composition, and increased with its incorporation. The electrical conductivity values for ABS with 5 wt% of CB were in the range of 10 −12 S. cm -1, while for hybrid composite and ABS with 5 wt% of CNT values between 10 -8 and 10 -5 S. cm -1 were observed. The EMI SE, for all patterns of printed samples, also increased with the increase of CNT amount and layer thickness, with values of around -16 dB for the composite with only CNT sample, and -14 dB for the hybrid sample. The PC pattern shows high anisotropy among the studied samples, presenting the highest EMI SE value for PC when measured horizontally (PC-H) and the lowest value when measured vertically (PC-V). The results obtained in this study show the real potential of applying FFF for the manufacturing of ABS/carbonaceous composites to be use in EMI shielding applications.